2020
DOI: 10.3390/f11111225
|View full text |Cite
|
Sign up to set email alerts
|

The Felling of Hung Up Trees—A Work Safety and Productivity Issue

Abstract: Research Highlights: The felling of hung up trees is considered by literature in the field as an activity with a high injury risk. The low work productivity in the felling of hung up trees is wrongly cited by workers in order to justify various more or less safe work techniques. Background and objectives: The purpose of this paper was to determine work productivity in the felling of hung up trees when this activity has a well-defined structure with stages and specific activities that would allow workers to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…The reduction in ineffective time can be accomplished by implementing a systematic work method, well planning, and organization . Campu et al (2020) and Bianchini et al (2021) reported that the success of rope-raising tool utilization in tree felling is determined by: a) professional training and formation, b) work organization, and c) utilization of appropriate materials and equipment.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in ineffective time can be accomplished by implementing a systematic work method, well planning, and organization . Campu et al (2020) and Bianchini et al (2021) reported that the success of rope-raising tool utilization in tree felling is determined by: a) professional training and formation, b) work organization, and c) utilization of appropriate materials and equipment.…”
Section: Discussionmentioning
confidence: 99%